The value of prenatal indicators in predicting adverse fetal outcomes in patients with ICP - Jiang, Jiahong; Zhou, Jun; Zhang, Litao; Li, Jie (Zeitschrift für Geburtshilfe und Neonatologie, 2025)
Search for laboratory markers that can predict adverse fetal pregnancy outcomes in patients with cholestasis of pregnancy.This was an observational case-control study conducted from December 2016 to December 2019. Pregnancy outcome data and maternal antenatal laboratory markers were collected in the intrahepatic cholestasis of pregnancy (ICP) (N=117) and normal pregnancy controls (N=100), laboratory indictors including aspartate aminotransferase (AST), alanine aminotransferase (ALT), alkaline phosphatase (ALP), γ-glutamyl transpeptidase (γ-GT), total bilirubin (TB), direct bilirubin (DB), total bile acids (TBA), cholyglycine (CG), prothrombin time (PT), international normalized ratio (INR), activated partial thromboplastin time (APTT), fibrinogen (FIB), etc. The ICP group was divided into an adverse outcome and normal outcome group according to fetal pregnancy outcomes. Descriptive statistics and regression analysis were performed on the prenatal indicators of the two groups to evaluate the association between prenatal laboratory indicators in ICP patients and adverse neonatal outcomes.ALT, TBA, CG, PT, APTT, hemoglobin, red blood cell distribution width, hematocrit, mean platelet volume, and platelet distribution width in ICP patients differed significantly from those in the normal control group, which led to premature birth, amniotic fluid pollution, low birth weight and other adverse outcomes. In terms of fetal outcomes, TBA [(39.16±35.70) μmol/L vs. (24.17±18.76) μmol/L], CG [(22.17±19.42) μg/mL vs. ( 13.91±13.18) μg/mL], DB [(22.17±19.42) μg/mL vs. (13.91±13.18) μg/mL] were higher than those in the normal outcome group, while fibrinogen was lower [(4.16±1.30) g/L vs. (4.78±0.91) g/L]; the difference was statistically significant. Multivariate logistic regression analysis showed that CG(OR=1.06, 95%CI:1.01~1.12, P=0.02, FIB(OR=0.54, 95%CI:0.31~0.92, P=0.02) was independently associated with the occurrence ofadverse fetal outcomes in ICP.Prenatal CG and FIB levels were independently associated with adverse fetal outcomes in patients with ICP.
Keywords: adverse neonatal outcome; cholyglycine; fibrinogen; intrahepatic cholestasis of pregnancy